2013
DOI: 10.1371/journal.pone.0073325
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach Identifying Hybrid Sterility QTL on the Autosomes of Drosophila simulans and D. mauritiana

Abstract: When species interbreed, the hybrid offspring that are produced are often sterile. If only one hybrid sex is sterile, it is almost always the heterogametic (XY or ZW) sex. Taking this trend into account, the predominant model used to explain the genetic basis of F1 sterility involves a deleterious interaction between recessive sex-linked loci from one species and dominant autosomal loci from the other species. This model is difficult to evaluate, however, as only a handful of loci influencing interspecies hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Although DM incompatibilities were originally linked to interactions between nuclear genes, miscommunication between nuclear and mitochondrial genomes has been implicated in yeast (Lee et al, 2008), drosophila and other insects (Dickman and Moehring, 2013; Foley et al, 2013), fish (Bolnick et al, 2008; Niehuis et al, 2008) and in primate xenomitochondrial cybrid cell lines (Bayona-Bafaluy et al, 2005). Previous studies in drosophila found male-specific infertility associated with mitochondrial polymorphism (Clancy et al, 2011; Innocenti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although DM incompatibilities were originally linked to interactions between nuclear genes, miscommunication between nuclear and mitochondrial genomes has been implicated in yeast (Lee et al, 2008), drosophila and other insects (Dickman and Moehring, 2013; Foley et al, 2013), fish (Bolnick et al, 2008; Niehuis et al, 2008) and in primate xenomitochondrial cybrid cell lines (Bayona-Bafaluy et al, 2005). Previous studies in drosophila found male-specific infertility associated with mitochondrial polymorphism (Clancy et al, 2011; Innocenti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic models have been developed that indicate that this type of fitness reduction may require at least two genetic changes-one from each species-but can be much more complex and be the result of multiple gene interactions (Johnson, 2000;Coyne and Orr, 2004). Multiple studies of HMS in the well-studied allopatric species pair Drosophila mauritiana and Drosophila simulans showed interactions of at least three genes or more (Johnson, 2000), and the identification of over 100 genes contributing to HMS on the X chromosome (Wu et al, 1996), as well as many genes on the autosomes (Tao et al, 2003;Araripe et al, 2010;Dickman and Moehring, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, combining X and Y chromosomes from different species has been shown to result in sterility, regardless of the autosomal complement (e.g. between D. simulans and D. mauritiana : [ 54 , 55 ], indicating that some aspect of heteromorphic chromosomes themselves may be responsible for F 1 sterility. Likewise, in mice, the pseudoautosomal region involved in pairing X and Y chromosomes is strongly associated with hybrid sterility when X and Y are from different species [ 56 ].…”
Section: Discussionmentioning
confidence: 99%